Implementation Of Discovery Learning In Increasing Students' Activity and Creativity - Andika, Andika; Wirawan, Gandung; Fuad, Akhmad Dzulkaul (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The The problem in this research is that students are less active and less creative in learning History due to the use of inappropriate teaching methods. The implementation of History learning as expected in the Merdeka curriculum can facilitate students to engage actively and creatively in the learning process. The discovery learning method is an alternative teaching method that can facilitate students to engage actively and more creatively in the History learning process. The objective of this research is to enhance the activity and creativity of learning History by using the discovery learning method among the students of class X IPS 1 at Madrasah Aliyah Darun Najah. The implementation of the research began in April and continued until May 2023. The subjects of this research are the students of class X IPS 1, with a total of 32 students. The indicators that will be studied in this research are student learning activity and creativity. The students' learning activity in the classical setting in cycle 1 was 57.81%, in cycle 2 it increased by 12.03% to 69.84%, and in cycle 3 it increased by 8.6% to 78.44%. The students' learning creativity in cycle 1 was 54.84%, in cycle 2 it increased by 11.57% to 66.41%, and in cycle 3 it increased by 10.93% to 77.34%. Based on the explanation above, it can be concluded that the application of the discovery learning method can enhance students' learning activity and creativity, especially in history subjects.